2016
DOI: 10.1099/jmmcr.0.005037
|View full text |Cite
|
Sign up to set email alerts
|

First case of mixed infection with Cryptococcus deuterogattii and Cryptococcus neoformans VNI in an Ivorian HIV-positive patient

Abstract: Introduction:Cryptococcal meningitis (CM) may be caused by several species of Cryptococcus. Case presentation: We describe a fatal case of CM in a HIV-positive patient from Ivory Coast infected by Cryptococcus neoformans VNI and Cryptococcus deuterogattii. Isolates were recovered from cerebrospinal fluid (CSF) prior to systemic antifungal treatment. Six isolates were studied (the entire culture plus five isolated colonies from it). Serotyping was performed via LAC 1 and CAP 64 gene amplification. Genotyping wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…URA5-RFLP and M13 PCR fingerprinting profile of one entire culture confirmed that the sample contained two different species, C. deuterogattii and C. neoformans VNI. 16 Interestingly, URA5-RFLP, M13 analysis and (GACA) 4 profiles associated with (GTG) 5 showed a high degree of polymorphism between isolates. These techniques generated 140 different genotypes grouped into 56 major molecular types (i.e.…”
Section: Serotyping and Genotypingmentioning
confidence: 95%
See 1 more Smart Citation
“…URA5-RFLP and M13 PCR fingerprinting profile of one entire culture confirmed that the sample contained two different species, C. deuterogattii and C. neoformans VNI. 16 Interestingly, URA5-RFLP, M13 analysis and (GACA) 4 profiles associated with (GTG) 5 showed a high degree of polymorphism between isolates. These techniques generated 140 different genotypes grouped into 56 major molecular types (i.e.…”
Section: Serotyping and Genotypingmentioning
confidence: 95%
“…Just one patient (53) had five isolates and one patient (57) had four.Repartition of the 56 major molecular types for the 363 studied isolates. Twenty-four patients(2,3,14,16,21,23,29,30,32,33,34, 35, 38, 42, 45, 47, 48, 51, 52, 54, 58, 59, 60, 61) exhibited Cryptococcus species with 2 to 4 different major molecular types in the same sample. The patient 19 was infected with two isolates with high flucytosine MICs (16 μg mL −1 ).…”
mentioning
confidence: 98%
“…To determine the molecular type, four primers designed for cloning LAC1 and a pair of primers for CAP64 22 were used in a slightly modified method as previously described 21,23 …”
Section: Methodsmentioning
confidence: 99%
“…The frequency of the MATα suggests it may confer an environmental and clinical advantage. Genetic studies have also shown that clinical isolates are more diverse and include the isolation of the rare environmental mating-type, MATa [103,123,124].…”
Section: Tolerance To the Limitation Of Nutrients And Watermentioning
confidence: 99%